2014
DOI: 10.1111/bjet.12197
|View full text |Cite
|
Sign up to set email alerts
|

Scaling informal learning at the workplace: A model and four designs from a large‐scale design‐based research effort

Abstract: Workplace learning happens in the process and context of work, is multi-episodic, often informal, problem based and takes place on a just-in-time basis. While this is a very effective means of delivery, it also does not scale very well beyond the immediate context. We review three types of technologies that have been suggested to scale learning and three connected theoretical discourses around learning and its support. Based on these three strands and an in-depth contextual inquiry into two workplace learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
0
37
0
2
Order By: Relevance
“…Ressaltou ainda que a aprendizagem nesses grupos ocorre de maneira informal, por meio de conversas entre os participantes, e formal, por meio de leituras dirigidas e da participação em eventos científicos. Embora efetivas e frutos de motivações intrínse-cas aos aprendizes, aprendizagens no trabalho -que são multiepisódicas, informais, baseadas em solução de problemas e em tempo real -não ultrapassam, no entanto, necessidades que emergem do trabalho cotidiano (LEY et al, 2014). Aprendizagens informais de docentes, em particular, realizam-se no seio de suas redes pessoais.…”
Section: Aprendizagem De Competências No Trabalhounclassified
See 1 more Smart Citation
“…Ressaltou ainda que a aprendizagem nesses grupos ocorre de maneira informal, por meio de conversas entre os participantes, e formal, por meio de leituras dirigidas e da participação em eventos científicos. Embora efetivas e frutos de motivações intrínse-cas aos aprendizes, aprendizagens no trabalho -que são multiepisódicas, informais, baseadas em solução de problemas e em tempo real -não ultrapassam, no entanto, necessidades que emergem do trabalho cotidiano (LEY et al, 2014). Aprendizagens informais de docentes, em particular, realizam-se no seio de suas redes pessoais.…”
Section: Aprendizagem De Competências No Trabalhounclassified
“…Essas duas conjecturas, no entanto, merecem ser testadas em outras amostras de instituições educacionais de nível superior no país. Em terceiro lugar, artigos internacionais e nacionais revisados indicam que docentes aprendem preferencialmente por mecanismos informais e em suas redes profissionais (ODELIUS et al, 2011;PATARAIA et al, 2014;LEY et al, 2014), o que tende a facilitar seus processos de transferência, quase que indiferenciando os estágios de aquisição e de transferência de competências (COELHO JÚNIOR; MOURÃO, 2011).…”
Section: Escalas De Desempenho No Cargounclassified
“…The informal learning practices evolved in professional communities have remained largely an unexplored territory. Lately, in EU 7th Framework project Learning Layers (http://learning-layers.eu) several empirical interview and design-based research studies have revealed some common practices among Healthcare and Construction stakeholders (Ley et al, 2014). In this paper we explore what role the recognition practices have in informal practice communities in the Q&A forums in Healthcare and Construction sectors.…”
Section: Introductionmentioning
confidence: 98%
“…One of the goals in lifelong learning policies and initiatives is scaling up the incidental and informal learning (Tynjala, 2008;Ley et al, 2014) that can be done by noticing, recording, sharing, and formally and socially recognizing those practices acquired at on the job training (Werquin, 2010), and uniting individual informal learning and organizational learning practices into an evolving knowledge creation and conversing systems (e.g. Nonaka & Takeuchi, 1995;Tammets et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation